Growth of Tilapia (Oreochromis niloticus) Juvenile strain Nirwana with Different Natural Feeding - rima oktavia kusuma; Muh. Sulaiman Dadiono; Kasprijo Kasprijo; Ren Fitriadi; Thomas Tere Yeru (PT. Artha GenetikaLab Indonesia, 2024)
The high cost of commercial feed in Nirwana tilapia aquaculture leads to elevated production costs and reduced profits. As a solution, the provision of natural feed is proposed as an alternative to reduce production expenses. This study aims to compare the growth of Nirwana tilapia fed with three different natural feeds: Tubifex sp., Chironomus sp. larvae, and maggots. The experiment was conducted using a completely randomized design with three replicates for each treatment. The feeding rate was 3% of the fish’s body weight, administered three times a day. The parameters measured included absolute biomass, absolute length gain, daily growth rate (Specific Growth Rate, SGR), survival rate (SR), and water quality during the 30-day rearing period. The results showed that feeding Nirwana tilapia with Tubifex significantly increased growth compared to the control group (commercial pellets), Chironomus larvae, and maggots. The absolute biomass from Tubifex feeding was 5.23 ± 0.89 g, absolute length was 4.2 ± 7.8 cm, SGR was 1.52 ± 0.33%, and SR was 90%. The next highest growth was seen in Chironomus larvae, followed by maggots, with the control yielding the lowest results.